The role of laparoscopy in the propaedeutics of gynecological diagnosis - Argentino, Gislaine Laperuta Serafim [UNESP]; Bueloni-Dias, Flávia Neves [UNESP]; Leite, Nilton José [UNESP]; Peres, Gustavo Filipov [UNESP]; Elias, Leonardo Vieira [UNESP]; Bortolani, Vitória Cristina [UNESP]; Padovani, Carlos Roberto [UNESP]; Spadoto-Dias, Daniel [UNESP]; Dias, Rogério [UNESP] (My University, 2019)
Purpose: To evaluate agreement between pre-and post-laparoscopy gynecological diagnosis in order to demonstrate the rationality of this minimally invasive technique use in gynecological propaedeutics. Methods: Retrospective chart review study conducted between March 2010 and October 2016 based on a convenience sample. 315 patients undergoing surgical laparoscopy at the Center of Gynecologic Endoscopy and Family Planning of Botucatu Medical School/ UNESP. Pre-and postoperative diagnoses were compared by the diagnosis agreement test considering the proportions of events. Results: Laparoscopy contributed to diagnosis in 59.6% of infertility cases (P>0.05), in 93.7% of chronic pelvic pain of undetermined origin (P<0.01) and conclusively elucidated the diagnosis of acute abdomen and the ruling out of tubo-ovarian abcess (P<0.05). Laparoscopy also increased the diagnosis of pelvic-abdominal adhesions in 76.7% (P>0.05). Conclusion: The use of laparoscopy considerably contributed to diagnostic elucidation, especially in cases of undetermined chronic pelvic pain.
Keywords: Education; Endometriosis; Female; Infertility; Laparoscopy; Medical; Pelvic pain; Techniques